Evaluasi Manajemen Portofolio Aset Kekayaan Bapak Ahmad - , Hutomo Rusdianto; , Prof. Dr. Tandelilin Eduardus, M.B.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This thesis is a study to manage wealth of High Net Worth Individuals (HNWI) in the family of Mr. Ahmad. This thesis discusses the client profile based on the type of risk-taking, evaluate portfolio asset allocation of wealth and formulate alternative solutions for client based on the pillars contained in the Wealth Management. Client in this thesis is 57 years old and works as a director at a private plantation companies. The first client financial goal is to diversify assets in order to minimize the risk of investment. The second, the client wants to increase cash flow and to increase the number of entry of liquid assets. The third, the client wanted to prepare for the cost of his son's wedding. Recommendations are given to clients by providing two alternative scenarios according to risk tolerance. The results obtained from these two scenarios are that first scenario can increase the wealth by Rp 1,129,818,000 and second scenario can increase client wealth by Rp 1,246,435,500. Both these scenarios have their advantages and disadvantages of each. The second difference lies in the selection of scenarios of investment instruments, so as to provide a wealth of different clients. After seeing the results of scenario one and scenario two, the client chose scenario two as a portfolio. Scenario two was chosen by the client to the consideration of the level of risk in any investment instrument and the results obtained.